The Geology of the Warsak Area, Peshawar, West Pakistan - Ahmad, Manzoor; Ali, K.S. Sheikh; Khan, Bahrawar; Shah, M.A.; Ullah, Ihsan (Journal of Himalayan Earth Sciences, 1969)
The Warsak Area, Peshawar, West Pakistan, has been geologically mapped and the petrography of the rocks described in detail. The area consists of a series of metasediments of the greenschist facies (slates, phyllites, mica schists, garnet schists, hornblende schists, calcareous schists and marbles), which have been divided into a Lower, Middle and Upper Series. On the eastern side the metasediments disappear under the alluvium of the Peshawar plain. They range from Siluro-Devonian to Upper Palaeozoic in age, and are intruded by sills of metagabbro and metadolerite (? Cretaceous) porphyritic microgranite (?Upper Cretaceous to Lower Tertiary) and the Warsak alkaline granite (?Lower Tertiary). The chemistry and alkaline nature of the granites (which contain aegirine, riebeckite and astrophyllite) is briefly discussed. The structure of the area is shown to be a northwards plunging syncline faulted on the east on the northern side of the Kabul River. The join/patterns and other structural features are described, and the economic geology of the area discussed.